Effect of surface chemistry of Fe-Ni nanoparticles on mechanistic pathways of azo dye degradation - Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Environmental Science & Technology, 2007)
The degradation of Orange G a monoazo dye, in aqueous solutions was investigated using as-synthesized and stored Fe-Ni bimetallic nanoparticles. Batch experiments with a nanocatalyst loading of 3 g/L showed complete. dye degradation (150 mg/L) after 10 min of reactiontime. HPLC-MS analysis of the degradation products showed that assynthesized nanoparticles reductively cleaved the azo linkage to produce aniline as the major degradation product. However, 1-year-stored nanoparticles showed an oxidative degradation of Orange G through a hydroxyl-radical induced coupling of parent and/or product molecules. XPS analysis in corroboration with HPLC-MS data showed that the surface chemistry between Fe and Ni in assynthesized and stored nanoparticles play a crucial role. in directing the mode of degradation. Reductive dye degradation using as-synthesized nanoparticles proceeded through hydride transfer from nickel, whereas formation of a Fe (2+) -Ni(0) galvanic cell in stored nanoparticles generated hydroxyl radicals from water in a nonFenton type reaction. The latter were responsible for the generation of radical centers on the dye molecule, which led to a coupling-mediated oxidative degradation of Orange G. The generation of hydroxyl radicals is further substantiated with radical quenching experiments using ascorbic acid indicating that stored nanoparticles degrade Orange G through a predominantly oxidative mechanism. HPLC-MS and XPS analysis of dye degradation using as-synthesized nanoparticles exposed to air and water confirmed that the reductive or oxidative degradation capability of Fe-Ni nanoparticles is decided by the time and type of catalyst aging process.

Efficiency and recycling capability of montmorillonite supported Fe-Ni bimetallic nanocomposites towards hexavalent chromium remediation - Kadu, Brijesh S.; Sathe, Yogesh D.; Ingle, Abhijit B.; Chikate, Rajeev C.; Patil, Kashinath R.; Rode, Chandrashekhar V. (Applied Catalysis B-Environmental, 2011)
The remediation of Cr(VI) from simulated water streams is investigated using Fe-Ni bimetallic nanoparticles (Fe-Ni NPs) and their nanocomposites prepared with montmorillonite (MMT) clay. These nanocomposites are characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Brunauer-Emmett-Teller (BET) surface area analyses. XRD analysis revealed proper dispersion as well as intercalation of Fe-Ni NPs in the clay matrix. TEM of nanocomposites showed the presence of spherical particles having a size of 20-40 nm. Batch experiments with a 25 mg L(-1) Cr(VI) solution and 2 g L-1 Fe-Ni NPs exhibited complete reduction of Cr(VI) within 10 min that follows first order reaction kinetics. Amongst 25%, 50%, 75% in situ and loaded nanocomposites, 75% compositions possess better activity with enhanced reduction capacity below pH 4 due to generation of reactive H center dot species. XPS analysis of nanocomposites after Cr(VI) treatment suggested that reduction process occurs through Cr(111) formation followed by its subsequent reduction to Cr(0). Their potentiality towards reusage is established from the recycling experiments that revealed the order of efficiency as 75% in situ > Fe-Ni NPs > 75% loaded nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cr(VI) remediation; Iron-nickel bimetallics; Montmorillonite; Nanocomposites; Recycling